2021
DOI: 10.4236/jacen.2021.101007
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Composting Spent Coffee Grounds by <i>Aspergillus sp</i> and <i>Aspergillus sp</i> in Aerobic Static Batch Temperature Control

Abstract: Spent Coffee Ground (SCG) is characterized by high organic content, in the form of insoluble polysaccharides bound and phenol compounds. Phenol compounds are toxic to nature and are a cause of environmental pollution. Composting method of this study is aerobic static batch composting with temperature control with adding activators of some fungi such as Aspergillus sp, and Penicillium sp. The purpose of the research is to fill the research gap from previous studies of spent coffee grounds compost, which require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…As opposed to nHAPs_CE, the XRD spectrum of nHAPs mediated by PPE showed sharper peaks, and this might be explained by differences in pH of the two extracts used. The pH of pomegranate peel extract was 4.83 [40], while that of coffee grounds extract was close to neutral (6.5 to 6.8) [41]. Changes in pH (from alkaline to acidic), temperature, and reaction time affect the degree of crystallinity [42].…”
Section: Nhap Preparation and Characterizationmentioning
confidence: 99%
“…As opposed to nHAPs_CE, the XRD spectrum of nHAPs mediated by PPE showed sharper peaks, and this might be explained by differences in pH of the two extracts used. The pH of pomegranate peel extract was 4.83 [40], while that of coffee grounds extract was close to neutral (6.5 to 6.8) [41]. Changes in pH (from alkaline to acidic), temperature, and reaction time affect the degree of crystallinity [42].…”
Section: Nhap Preparation and Characterizationmentioning
confidence: 99%
“…Spectroscopic techniques have also been reported in SCG composting for fertilizers to identify the compost maturity [19,59] and organic matter humification [60]. SCG applications as agriculture fertilizers are discussed in Section 4.…”
Section: Spectroscopic Analysismentioning
confidence: 99%
“…Recent studies showed that SCGs have excellent potential to be used in agriculture because of their high amount of nutrients and low risk of heavy metal contamination [14,15]. Therefore, SCGs have already been reported to be a soil amendment or a top dressing to improve soil quality and control weeds [12,16,17], as well as composting with animal manure and other wastes to improve soil quality, enhance plant growth, and avoid intoxicating the soil [18,19]. Environmental pollution problems due to solid waste and new environmental regulations have forced the industry to pay more attention to waste management.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of activators (bacteria and fungi) also plays an important role in the degradation rate of raw materials rich in lignin and hemicellulose such as spent grains. Adding specific fungi like Aspergillus and Penicillium would degrade lignin and hemicellulose faster [16].…”
Section: Total Carbon Toc and Organic Matter Ommentioning
confidence: 99%